A Basis Set for Characterizing Transient Random Phenomena - Howard, Roy (American Institute of Physics, 2009)
An orthogonal basis consistent with transient random phenomena is proposed and applied to market data and 1/ƒ noise. For 1/ƒ noise the power-rate spectrum is flat. The basis set leads to a power-rate spectrum and can be used to facilitate the detection of specific signal forms.